President’s Message: Motivation/Behaviour - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1993)
Motivation comes from a Greek word “to move”, which refers to a whole process whereby a person is energized to behave. Behaviour is seen as purposeful, goal directed and based on conscious intentions which can be negative or positive. Motivation can be looked at as an energy ﬂow of an individual, directed at or through a given behaviour. If one makes a wrong assumption, then one's behaviour will be wrong. Assumptions should always be checked outbefore reaching conclusions. A person with leadership responsibility might ask what impact do I have on others?